Respon Pertumbuhan Tanaman Iler (Coleus scutellarioides (L.) Benth) pada Kondisi Cekaman Kekeringan terhadap Inokulasi Fungi Mikoriza Arbuskular (FMA) - Eva Proditus Sianturi; Budiman Budiman; Moh. Ega Elman Miska (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Iler plant (Coleus artopurporeus L benth) is a plant that was originally cultivated as an ornamental plant and then developed as a medicinal plant because it contains flavonoids and anthocyanins. Drought stress is a major environmental problem that causes various changes in plant morphological, metabolic and physiological functions. Utilization of Arbuscular Mycorrhizal Fungi (AMF) is an effort to support the growth and development of iler plants in drought stress conditions. This study aims to determine the effect of AMF inoculation on the growth of iler plants under drought stress conditions, determine the optimal level of drought stress for ilher plant growth, and determine the best interaction between AMF inoculation and the level of drought stress on the growth of iler plants. The design used in this study was a completely randomized factorial 2-factor design. The first factor is AMF inoculation consisting of 2 levels, namely, without administration of AMF inoculum and AMF inoculum administration. The second factor is drought stress consists of 3 levels namely, 100% field capacity, 90% drought stress, and 45% drought stress. The results showed the effectiveness of the AMF inoculum test was able to increase the growth of iler plants based on parameters plant height, number of leaves, number of branches, leaf area, root length, root volume, root dry weight, number of spores and root infection. The optimal level of drought stress for iler plant growth is 90% drought stress, it is based on the parameters of plant height, number of leaves, number of branches, leaf area, root length, number of spores and root infection. There is the best interaction between AMF inoculation and 90% drought stress level on the growth of iler plants. These interactions can increase plant height, leaf area, number of spores and root infection. Keywords: arbuscular mycorrhizal fungi (FMA), drought stress, iler plants